Prinzmetal Angina with Pan Hypopituitarism- A Case Report - Arzu, Jahanara; Rahmanh, HN Ashiqur; Selim, Mohammad Daniel; Apsara, Nusrat Biswas; Sheikh, Naveen; Ahmed, Sheikh Foyez; Ahmed, Chowdhury Meshkat (University Heart Journal, 2022)
A 31yrs old female teacher came to our emergency department with the complaints of severe retro sternal & compressive type chest pain radiated to the left arm, back and jaw. Pain was partially relieved by rest and associated with vomiting & nausea but no breathlessness. She also reported episodes of angina in previous couple of months. On admission, there was ST-segment elevation that last for few minutes and later progressively resolved. But troponin level was high. Patient was undergone Coronary angiogram and was diagnosed as stress induced cardiomyopathy (SICM), as Coronary Angiogram showed normal epicardialcoronary arteries. Serial ECG was carried out which showed resolved ST elevation. Holter monitoring showed severe ST-segment changes during an angina episode. She had no history of substance abuse or recreational drug use.Before discharge we started oral calcium antagonist and there wasn’t any further episode of angina or ST changes on follow up after two months. University Heart Journal 2022; 18(2): 125-127